Improving animal welfare status and meat quality through assessment of stress biomarkers: A critical review. (March 2023) - Kumar, Pavan; Ahmed, Muideen Adewale; Abubakar, Abubakar Ahmed; Hayat, Muhammad Nizam; Kaka, Ubedullah; Ajat, Mokrish; Goh, Yong Meng; Sazili, Awis Qurni
Abstract: Stress induces various physiological and biochemical alterations in the animal body, which are used to assess the stress status of animals. Blood profiles, serum hormones, enzymes, and physiological conditions such as body temperature, heart, and breathing rate of animals are the most commonly used stress biomarkers in the livestock sector. Previous exposure, genetics, stress adaptation, intensity, duration, and rearing practices result in wide intra- and inter-animal variations in the expression of various stress biomarkers. The use of meat proteomics by adequately analyzing the expression of various muscle proteins such as heat shock proteins (HSPs), acute phase proteins (APPs), texture, and tenderness biomarkers help predict meat quality and stress in animals before slaughter. Thus, there is a need to identify non-invasive, rapid, and accurate stress biomarkers that can objectively assess stress in animals. The present manuscript critically reviews various aspects of stress biomarkers in animals and their application in mitigating preslaughter stress in meat production. Highlights: A rapid assessment of preslaughter stressors is crucial for to allevate stress. Various behavioral, physiological, metabolomics, and proteomics expressions are used for assessing the preslaughter stress. A rapid, sensitive, and accurate assessment of stress biomarkers in modern high throughput abattoirs is the need of the hour.